Hubungan antara Penggunaan Kontrasepsi Oral dengan Kejadian Hipertensi pada Wanita Usia Subur di Puskesmas Kalumata - Muhammad Wahyu Tryadi; Fera The; Ryan Rinaldy Marsaoli (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Hypertension is defined as a medical condition in which blood pressure persistently exceeds the normal limit of ≥140/90 mmHg. In 2018, the prevalence of hypertension in Indonesia reached 34.11%. One significant contributor factor to the development of hypertension is the use of oral contraceptives, which can influence the renin-angiotensin-aldosterone (RAA) system and promote atherosclerosis, leading to elevated blood pressure. This quantitative study aimed to investigate the association between oral contraceptive use and hypertension among women of reproductive age. An observational cross-sectional design was employed. A total of 44 respondents were selected using incidental sampling, and data were analyzed using the Chi-square test. The results showed that 56.8%of respondents were non-hypertensive , 61.4% used combined oral contraceptives, 61.4% were aged >35 years old , 54.5% had used contraception for ≥ 2years , and were overweight (59.1%). Bivariate analysis demonstrated a significant association between oral contraceptive use and hypertension (p = 0.03), as well as between body mass index and hypertension (p = 0.02).to Specifically, women using combined oral contraceptives were found to have a 4.063 times higher risk of developing hypertension compared to those using oral progestins. This increased risk may be attributed to the estrogen components, which can affect the RAA system and contribute to elevated blood pressure through angiotensin II-mediated mechanism. In contrast, no significant association was observed between age and the incidence of hypertension in this population (p = 0.143). Similarly, the duration of oral contraceptive use was not significantly associated with hypertension, (0.107), a finding that may be influenced by the relatively small sample size. Keywords : body mass index, duration, hypertension, oral contraceptive DOI : 10.35990/mk.v9n1.p45-56